2016
DOI: 10.1016/j.applthermaleng.2016.02.070
|View full text |Cite
|
Sign up to set email alerts
|

Thermal management for high power lithium-ion battery by minichannel aluminum tubes

Abstract: Lithium-ion batteries are widely used for battery electric (all-electric) vehicles (BEV) and hybrid electric vehicles (HEV) due to their high energy and power density. Battery thermal management system (BTMS) is crucial for the performance, lifetime, and safety of lithium-ion batteries. In this paper, a novel design of BTMS based on aluminum minichannel tubes is developed and applied on a single prismatic Li-ion cell under different discharge rates. Parametric studies are conducted to investigate the performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(77 citation statements)
references
References 34 publications
0
77
0
Order By: Relevance
“…Jin et al developed a thermal management system for power batteries that used an oblique mini‐channel liquid cold plate to enhance heat transfer coefficient. Lan and Xu designed a solution using aluminum mini‐channel tubes for high‐power Li‐ion battery thermal management; simulations showed that the system was capable to control the temperature difference within the battery less than 1°C. Despite of the extensive research, an urgent need remains for developing safe, high‐efficient, and cost‐effective thermal management systems.…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al developed a thermal management system for power batteries that used an oblique mini‐channel liquid cold plate to enhance heat transfer coefficient. Lan and Xu designed a solution using aluminum mini‐channel tubes for high‐power Li‐ion battery thermal management; simulations showed that the system was capable to control the temperature difference within the battery less than 1°C. Despite of the extensive research, an urgent need remains for developing safe, high‐efficient, and cost‐effective thermal management systems.…”
Section: Introductionmentioning
confidence: 99%
“…19 A battery thermal management system (BTMS) is needed since extreme temperature can significantly affect safety and durability of EVs. For mitigating these potential hazards, Xu et al 22 and Lan et al 23 developed a novel BTMS based on aluminum mini-channel tubes and applied it to a single prismatic Li-ion battery under different discharge rates. For mitigating these potential hazards, Xu et al 22 and Lan et al 23 developed a novel BTMS based on aluminum mini-channel tubes and applied it to a single prismatic Li-ion battery under different discharge rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the fact that forced air cooling, liquid cooling and heat pipe cooling systems in a battery module present effective performance of temperature control and uniformity, the design of the structure in the system is relatively complex [8,9], especially for liquid cooling due to the risk of refrigerant leakage [10,12]. Moreover, additional components of active energy supply such as pumps and fans, which increase energy consumption, are required for air cooling and liquid cooling [26,27]. Thus, passive cooling technology represented by PCM cooling has been considered as the most potential alternative of the above traditional BTM system [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%